2006
DOI: 10.3928/02793695-20060701-06
|View full text |Cite
|
Sign up to set email alerts
|

Helping Parents with Mental Illnesses and their Children: A Call for Family-Focused Mental Health Care

Abstract: <h4></h4> <p>Recent statistics indicate that nearly one quarter of American adults have been diagnosed with a mental illness (Egan &amp; Asher, 2005). This means many of these adults are parents affected by a mental illness while trying to raise their children. Nurses in many health care settings, particularly pediatrics, public health, schools, emergency rooms, and mental health, often see the damaging influence of parental mental illness on children. As the largest number of health care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 11 publications
1
7
0
1
Order By: Relevance
“…The results of this study support the idea that has been proposed by several other researchers (2, 15, 22), namely that nurses can play a unique role in a variety of ways, and they can also become key‐players in the initiatives for these children and their families. One notable example of how nurses can help children to cope could be teaching children, individually and in groups, about their parent’s illness and treatment (22, 23).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The results of this study support the idea that has been proposed by several other researchers (2, 15, 22), namely that nurses can play a unique role in a variety of ways, and they can also become key‐players in the initiatives for these children and their families. One notable example of how nurses can help children to cope could be teaching children, individually and in groups, about their parent’s illness and treatment (22, 23).…”
Section: Discussionsupporting
confidence: 88%
“…It may also indicate that the recognition of these children is not seen as a part of regular nursing practice; but conversely, belongs to nurses who have further education or even a ‘specific job description’. The results of this study, as well as other recent studies (15, 17, 21, 22), suggest that a family‐centred approach is necessary in order to assess family needs, involving the needs of the children.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…In Australia, some studies have asked parents, children and healthcare professionals about the support needs of these families (Cowling 1999, Fudge & Mason 2004, Maybery et al. 2005, Mason & Suberi 2006). However, Bates & Coren (2006), in their extensive systematic mapping of the research of parental mental health problems and interventions, found that very few nursing studies are available in which nurses take the family's relationships and support network into account in families affected by parental mental disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Hilfs-und Unterstützungsangebote sind daher nicht auf die Kinder psychisch kranker Eltern zu beschränken, sondern vielmehr auf die betroffenen Elternteile und deren Partner (bzw. weitere Angehörige) auszuweiten (11,12). Sie sollten daher zum einen an den Bedürfnissen des gesamten Familiensystems orientiert sein.…”
unclassified